A COMPARATIVE VIEW ON THE REGULATION OF GOAL-SETTING CATEGORIES IN THE CRIMINAL PROCEDURE LEGISLATION OF POST-SOVIET STATES - GRIGORYEV Viktor Nikolaevich; ZINCHENKO Igor Anatolyevich (Правовое государство: теория и практика, 2024)
The authors of the article analyze one of the trends in the criminal procedure legislation of the Russian Federation and neighboring countries, formed in the period of its codification in 1958–1961, which consists in fixing in the texts of laws such categories as the purpose and objectives of this branch of law or the activity regulated by it. The legal techniques used by legislators in Post-Soviet states to reflect these categories in regulatory legal acts are contradictory and sometimes polar. The law and jurisdictional activity are heterogeneous in terms of the subject of legal regulation, and most importantly – in terms of the content of the norms defining their status. Methods: empirical methods of description and interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic, comparative legal. Based on the conducted research and the author’s approach to the solution of the problem, the wording of a new structural unit – the article of the Code of Criminal Procedure of the Russian Federation «The Purpose and Objectives of Criminal Procedure Legislation» is formulated, which can be taken into account in the course of forthcoming lawmaking.